(untitled) - Perry, Douglas L. (New York, 2005)
Formal verification is a powerful new digital design method. In this cutting-edge tutorial, two of the field's best known authors team up to show designers how to efficiently apply Formal Verification, along with hardware description languages like Verilog and VHDL, to more efficiently solve real-world design problems.
Keywords: Integrated circuits,Electronic circuits; Verification,Testing